The Collaboration Between the Bayur Port Customs Office and the Local Government of Padang Pariaman Regency in Combating Illegal Cigarettes - Nurqoriah, Handayani; Frinaldi, Aldri (The Future of Education Journal, 2026)
The increasing crackdown on illegal cigarettes at the regional level demands cross-institutional synergy. This study aims to analyze the collaboration process between the Bayur Port Customs Office and the Local Government of Padang Pariaman Regency in tackling the circulation of illegal cigarettes. The analysis is based on the five dimensions of collaboration framework by Thomson and Perry (2006), which include governance, administration, autonomy, mutuality, as well as norms of trust and reciprocity. This research employs a descriptive qualitative method. Data collection was conducted through in-depth interviews with stakeholders from the Bayur Port Customs Office, the Civil Service Police Unit (Satpol PP), and the Regional Financial Management Agency (BPKD) of Padang Pariaman Regency. The findings indicate that the collaboration operates pragmatically and functionally asymmetrically. Weaknesses in governance and administrative dimensions, characterized by the absence of written agreements (MoU/SOP) and the dominance of informal communication, are compensated by strong institutional autonomy and interpersonal trust between actors. The mutuality formed is calculative, driven by the need to absorb 10% of the Tobacco Excise Revenue Sharing Fund (DBHCHT) for law enforcement. Supporting factors include the complementarity of resources, where the Bayur Port Customs Office provides legal authority, while the Local Government of Padang Pariaman Regency offers social legitimacy and sociological proximity to the community. In contrast, inhibiting factors to collaboration include the lack of formal institutionalization and regional fiscal rigidity. The conclusion of this study indicates that although the collaboration is effective in practice, it faces collaborative fragility that could stagnate if there is a change in officials. Therefore, institutionalizing the cooperation through an Annual Work Plan (RKT) and intelligence data exchange is necessary for the effectiveness of socialization activities.